3‐Hydroxyisobutyric acid dehydrogenase deficiency: Expanding the clinical spectrum and quantitation of D‐ and L‐3‐Hydroxyisobutyric acid by an LC–MS/MS method. Issue 3 (7th March 2022) - Sasarman, Florin; Ferdinandusse, Sacha; Sinasac, David S.; Fung, Ernest; Sparkes, Rebecca; Reeves, Melanie; Rombough, Catherine; Sass, Jörn Oliver; Voit, Renate; Ruiter, Jos P. N.; Koster, Janet; Waterham, Hans R.; et al.
Abstract: A deficiency of 3‐hydroxyisobutyric acid dehydrogenase (HIBADH) has been recently identified as a cause of primary 3‐hydroxyisobutyric aciduria in two siblings; the only previously recognized primary cause had been a deficiency of methylmalonic semialdehyde dehydrogenase, the enzyme that is immediately downstream of HIBADH in the valine catabolic pathway and is encoded by the ALDH6A1 gene. Here we report on three additional patients from two unrelated families who present with marked and persistent elevations of urine L‐3‐hydroxyisobutyric acid (L‐3HIBA) and a range of clinical findings. Molecular genetic analyses revealed novel, homozygous variants in the HIBADH gene that are private within each family. Evidence for pathogenicity of the identified variants is presented, including enzymatic deficiency of HIBADH in patient fibroblasts. This report describes new variants in HIBADH as an underlying cause of primary 3‐hydroxyisobutyric aciduria and expands the clinical spectrum of this recently identified inborn error of valine metabolism. Additionally, we describe a quantitative method for the measurement of D‐ and L‐3HIBA in plasma and urine and present the results of a valine restriction therapy in one of the patients.